Survey of Lay-Up Skill Levels Among Basketball Extracurricular Students at SMP Negeri 17 Kota Bengkulu - Gayane Vatona; Nurian Aprilia Windasari; Zacky Zell Vano; Muhammad Royhan; Aldi Prasetyo; Martiani Martiani (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to describe and map the lay-up skill levels of students in the basketball extracurricular program at SMP Negeri 17 Bengkulu City. This was a descriptive quantitative study using a survey method. The population and sample consisted of all 25 active basketball extracurricular students, selected using total sampling. The research instrument utilized a lay-up skill test consisting of 10 attempts (5 from the right side and 5 from the left side). The data were analyzed using descriptive percentage statistics. The results indicated that the students' lay-up skills fell into the